Impact of AAOIFI’s Governance Standards on Quality Corporate Governance by Islamic Financial Institutions - Rabiu Bala, Najaatu; Salihu , Maimuna Adamu; Dandago, Kabiru Isa; Kyari, Adam Konto (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
This study examines the impact of AAOIFI’s governance standards on quality the corporate governance practices by Islamic Financial Institutions. The paper is purely a literature-review-based research work where adequate literature relevant to the study are reviewed and the AAOIFI Governance Standards are studied with a view to finding out how compliance with the standards by the IFIs could translate into achievement of their set objectives, especially the objective of growing up the wealth of the shareholders. A rundown was given to the thirteen (13) governance standards (GS 1-13) issued by the AAOIFI, to show importance compliance with them would make the IFIs more “lovely” and more wealth-creating. It was found that AAOIFI’s governance standards have positive impact on the corporate governance practices of IFIs, as the standards lead to a certain degree of consistency in products and services offered by IFIs and the promotion of standardized practices at country level, as well as at the global level. The study also revealed that scholars in the field of Corporate and Public Governance have less interest in conducting studies on the AAOIFI’s GS the way they pay research attention to conventional Corporate Governance and Public Governance matters. The study recommended that AAOIFI should ensure that scholars and professionals in the field of Corporate and Public Governance are encouraged to pursue high level research on the practicality of all the 13 Governance Standards through provision of Research Grant, seminars and workshops.